Income effects of disability benefits - Sebastian Becker; Annica Gehlen; Johannes Geyer; Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
We provide novel evidence about the incentive and welfare effects of an increase in the generosity of disability benefits. Importantly, a unique policy variation in Germany allows us to isolate the income effect of a change in benefit generosity. We leverage this quasi-experimental policy variation using an RD design to estimate the effect of increasing disability benefits on employment, earnings, labor market transitions, and mortality outcomes using administrative data on the universe of new disability benefit recipients. Contrary to previous literature, our analysis reveals no significant impact on the employment and earnings of DI recipients due to the increased benefits. However, we find a sizable effect of the probability of returning to the labor market. We find no effects on recipient mortality six years after benefit award, but estimates imply a notable reduction in poverty risk, highlighting meaningful welfare implications of increased generosity.
Keywords: H55; I12; J22; J26; 330; disability insurance; pension reform; wealth effect; labor supply; mortality; RDD